Effect of Peat Addition on Sorption and Leaching of Triazole Fungicides in Oran Soils - Kahina Aït Hammi; Elías Nieto-Latorre; María D. Ureña-Amate; María M. Socías-Viciana; Hafida Miloudi; Naoufal Debbagh-Boutarbouch (Journal of Chemistry)
In this paper, the authors treat the impact of peat amendment on sorption and leaching of fungicides penconazole and flusilazole in two Algerian topsoil samples (Misserghine and Es-Senia). The batch equilibration technique was applied for adsorption experiments, and leaching was tested through soil column simulated experiments under laboratory conditions. Adsorption data fitted well to the Freundlich and linear models, showing the higher adsorption capacity of the Es-Senia soil for both fungicides, the order of sorption being flusilazole > penconazole. Organic amendments increased the adsorption of both fungicides especially for the soil with the lower organic matter (OM) content, obtaining a good correlation of this parameter with Kf, thus implying that OM is the principal soil parameter governing fungicides adsorption. Results of soil column experiments indicated that peat amendment decreased leaching of both pesticides in the soils studied. So, the use of organic addition might be an effective management practice for controlling potential pollution of penconazole and/or flusilazole to the environment.